Sensitivity and temperature behavior of a novel z-axis differential resonant micro accelerometer. (2nd February 2016) - Comi, C; Corigliano, A; Langfelder, G; Zega, V; Zerbini, S
Abstract: The present work concerns the operating principle and a thorough experimental characterization of a new polysilicon resonant micro accelerometer for out-of-plane measurements, fabricated using an industrial surface micromachining technique. This device is characterized by differential resonant sensing, obtained from the variation of the electrostatic stiffness of two torsional resonators under the application of an external acceleration. The sensitivity, defined as the differential shift in resonance frequencies per gravity unit (lg  =  9.8 m s −2 ), is of about 10 Hz g −1 when operated at a DC bias of 1.5 V only. Over an acceleration range larger than 10 g, the deviation from linearity is lower than 1% and the cross-axis rejection is larger than 34 dB. The resonators temperature coefficients of frequency, in the order of  −29 ppm C −1, are matched within about 0.1%, resulting in linear offset drifts against temperature lower than 5 mg up to 95 C in absence of any digital compensation.